설진 유효 분석을 위한 혀의 기하정보 추출 방법 - 은성종(Sung-Jong Eun); 김재승(Jae-Seung Kim); 김근호(Keun-Ho Kim); 황보택근(Taeg-keun Whangbo) (한국콘텐츠학회 논문지, 11(12), 2011)
In Oriental medicine, the status of a tongue is the important indicator to diagnose the condition of internal organs in a body. A tongue diagnosis is not only convenient but also non-invasive, and therefore widely used in Oriental medicine. But tongue diagnosis has some problems that should be objective and standardized, it also exhaust the diagnosis tool that can help for oriental medicine doctor's decision-making. In this paper, to solve the this problem we propose a method that calculates the tongue geometry information for effective tongue diagnosis analysis. Our method is to extract the tongue region for using improved snake algorithm, and calculates the geometry information by using convex hull and In-painting. In experiment, our method has stable performance as 7.2% by tooth plate and 8.5% by crack in region difference ratio. 한의학에서 혀의 상태는 인체의 건강 상태를 진단하는 중요한 지표로 활용된다. 이러한 혀의 상태를 진단하는 설진은 편리할 뿐 아니라 비침습적이므로, 한의학에서 널리 활용되고 있다. 그러나 설진은 객관화와 표준화라는 관점에서 문제가 있으며, 한의사의 의사결정에 도움을 줄 수 있는 도구도 부족한 실정이다. 본 논문은 이러한 문제점을 해결하기 위해, 설진 유효 분석을 위한 혀의 기하정보를 자동으로 계산하는 방법을 제안한다. 제안된 방법은 개선된 스네이크(Snake) 방법을 통해 혀를 검출하고 컨벡스 헐(Convex Hull)과 인페인팅 방법을 이용하여 객관적인 기하 정보를 추출하였다. 제안 알고리즘의 성능평가로 치흔의 경우 7.2%, 균열의 경우 8.5%의 영역 차이 비율로 안정적인 결과가 도출되었다.